A logic-based decision support system for the diagnosis of headache disorders according to the ICHD-3 international classification. Issue 6 (November 2020) - COSTABILE, ROBERTA; CATALANO, GELSOMINA; CUTERI, BERNARDO; CONCETTA MORELLI, MARIA; LEONE, NICOLA; MANNA, MARCO
Abstract: Decision support systems play an important role in medical fields as they can augment clinicians to deal more efficiently and effectively with complex decision-making processes. In the diagnosis of headache disorders, however, existing approaches and tools are still not optimal. On the one hand, to support the diagnosis of this complex and vast spectrum of disorders, the International Headache Society released in 1988 the International Classification of Headache Disorders (ICHD), now in its 3rd edition: a 200 pages document classifying more than 300 different kinds of headaches, where each is identified via a collection of specific nontrivial diagnostic criteria. On the other hand, the high number of headache disorders and their complex criteria make the medical history process inaccurate and not exhaustive both for clinicians and existing automatic tools. To fill this gap, we present head-asp, a novel decision support system for the diagnosis of headache disorders. Through a REST Web Service, head-asp implements a dynamic questionnaire that complies with ICHD-3 by exploiting two logical modules to reach a complete diagnosis while trying to minimize the total number of questions being posed to patients. Finally, head-asp is freely available on-line and it is receiving very positive feedback from the group of neurologists that is testing it.